A semi-dry viscoelastic sealant and its preparation method and application
By using polyisobutylene and polyisobutyleneamine resins and microcapsules with embedded polyisocyanate in semi-dry viscoelastic sealant, the problem of thread stuck when the sealant is directly used is solved, and good sealing performance is maintained in seawater environments .
Patent Information
- Application Number
- CN202311138517.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-09-05
AI Technical Summary
The existing semi-dry viscoelastic sealant can easily cause threads to get stuck when used directly, affect installation, and have poor sealing effect when subjected to alternating loads in seawater environments.
Polyisobutylene and polyisobutyleneamine are used as main resins, and microcapsules with embedded polyisocyanate are added. The microcapsules are broken during thread installation. The internal polyisocyanate core material flows out and the resin chain extends to form a high molecular weight compound, which is converted into semi-dry Viscoelastic sealant.
The problem of thread jamming is avoided, the thread installation is ensured smoothly, and good sealing performance and corrosion resistance are maintained when subjected to large alternating loads in seawater environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a semi-dry viscoelastic sealant and a preparation method and application thereof. Background Art
[0002] Threaded connectors are widely used in the shipbuilding field and usually bear large alternating loads. Threaded connectors that are immersed in seawater for a long time are prone to thread corrosion under the action of seawater corrosion and alternating loads, which leads to failure and pull-off of the connector. Sealing the threads to isolate the medium from penetration is an important technical means to prevent thread corrosion. Compared with conventional sealing by wrapping polytetrafluoroethylene raw tape, the sealant has good fluidity and can penetrate into the thread gap during use. After curing, it forms an elastic, semi-dry or rigid sealing layer with high sealing reliability. It has been widely used in threaded connection sealing in many fields such as marine equipment, petrochemicals, aviation, and aerospace. Thread sealants can be divided into dry sealants, non-drying liquid sealants, and semi-dry viscoelastic sealants according to their properties.
[0003] Dry sealants are applied to the threaded parts. After assembly, they undergo a curing reaction to form a dry solid sealing material. Thread sealant is a product of this type. It is often used for bolt protection to prevent the threads from biting and isolating the sealing medium. However, when the cured dry sealant is used for threaded connections that bear alternating loads, it is easy to crack and break under fatigue vibration and lose the sealing effect. Non-drying liquid sealants are suitable for static sealing. The principle is to use the adhesion, fluidity and monomolecular film rebound effect of liquid sealants to form a continuous liquid isolation film in the narrow gap of the required sealing interface to block the intrusion of foreign substances such as water. However, when liquid sealants are used for threaded connections that bear alternating loads, the liquid film is easily squeezed out and loses continuity, resulting in reduced sealing effect or even loss of sealing effect. Semi-dry viscoelastic sealants have the advantages of both non-drying liquid sealants and dry sealants. They have good anti-vibration and impact performance through good viscoelasticity, self-adhesion and certain self-repairing functions. They are not easily squeezed out under alternating pressure and repeated deformation, and can maintain excellent sealing performance for a long time.
[0004] Polyisobutylene has high main chain saturation and good structural stability. It has good dielectric sealing, electrical insulation, lubrication, acid and alkali resistance, corrosion resistance, ozone resistance and UV aging resistance. By using small molecule polyisobutylene with active groups for chain extension and cross-linking reaction, semi-dry viscoelastic sealants with excellent comprehensive properties such as sealing, corrosion resistance, fatigue resistance, lubrication and easy installation can be prepared. However, the current semi-dry viscoelastic sealants are prone to thread jamming and installation problems when used directly. Summary of the invention
[0005] In view of the above-mentioned deficiencies, the object of the present invention is to provide a semi-dry viscoelastic sealant and its preparation method and application. The sealant not only has good viscoelasticity, self-adhesion and self-repairing functions, but can also be used to meet the sealing and corrosion protection requirements of threaded connections subjected to large alternating loads in seawater environments, and the problem of thread jamming will not occur during the installation process.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] On the one hand, the present invention provides a semi-dry viscoelastic sealant, which includes, by mass: 45-60 parts of polyisobutylene resin, 25-40 parts of polyisobutylene amine, 15-25 parts of polyisocyanate microcapsules, 10-20 parts of lubricating filler, 5-10 parts of reinforcing filler, 20-30 parts of color filler, 4-8 parts of rust-proof filler, 1-2 parts of thickener, 0.3-0.6 parts of dispersant, and 2-4 parts of corrosion inhibitor.
[0008] Preferably, the polyisocyanate microcapsules are polyisocyanate microcapsules encapsulated by urea-formaldehyde resin.
[0009] Preferably, the polyisocyanate is hexamethylene diisocyanate (HDI trimer).
[0010] Preferably, the method for preparing polyisocyanate microcapsules comprises the following steps:
[0011] The urea, formaldehyde and alkaline pH regulator are mixed and subjected to condensation reaction to obtain a urea-formaldehyde resin prepolymer;
[0012] The emulsifier is dissolved in water to obtain a continuous phase solution, and then the polyisocyanate is added to the continuous phase solution and dispersed at high speed to obtain a polyisocyanate emulsion;
[0013] The urea-formaldehyde resin prepolymer, polyisocyanate emulsion and acidic pH regulator are mixed and then subjected to curing reaction to obtain urea-formaldehyde resin-wrapped isocyanate microcapsules.
[0014] Preferably, in the preparation of the urea-formaldehyde resin prepolymer, the mass ratio of urea to formaldehyde is 5:(10-18), and the alkaline pH regulator is a 10% sodium carbonate aqueous solution.
[0015] Preferably, the pH value of the condensation reaction is 8 to 9, the temperature of the condensation reaction is 60 to 90° C., and the reaction time is 1 to 4 hours.
[0016] Preferably, in the preparation of the polyisocyanate emulsion, the emulsifier is at least one of Tween-80, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, gum arabic, and alkylphenol polyoxyethylene ether, and its added amount is 3% to 5% of the mass of the polyisocyanate, and the mass ratio of polyisocyanate to water in the polyisocyanate emulsion is 1:(8 to 10).
[0017] Preferably, the acidic pH regulator is glacial acetic acid; the pH value of the curing reaction is 2 to 3, the reaction temperature is 50 to 70° C., and the reaction time is 2 to 3 hours.
[0018] Preferably, after the solidification reaction is completed, the solidified product suspension is centrifuged, washed and dried in sequence.
[0019] Preferably, the molecular weight of the polyisobutylene resin is 2000-2800, and the molecular weight of the polyisobutylene amine is 800-1000.
[0020] On the other hand, the present invention also provides a method for preparing the semi-dry viscoelastic sealant, comprising the following steps:
[0021] The polyisobutylene resin, polyisobutylene amine, lubricating filler, reinforcing filler, pigment filler, rust-proof filler, thickener, wetting dispersant and corrosion inhibitor are mixed, dispersed evenly, and ground to a fineness of less than 30 μm to obtain component A;
[0022] Polyisocyanate microcapsules are added to the A component and mixed evenly to obtain the semi-dry viscoelastic sealant.
[0023] In a third aspect, the present invention provides a use of the above-mentioned semi-dry viscoelastic sealant in a threaded connection.
[0024] Preferably, the above application includes: coating the semi-dry viscoelastic sealant provided in the above technical solution on the surface of the thread to be installed, the coating amount of the sealant is greater than the actual filling amount of the thread, after the thread is installed, excess sealant should be squeezed out, and then the extruded excess sealant is wiped clean, and the thread is left to stand after installation until the sealant on the inner wall is converted into a semi-dry viscoelastic state.
[0025] The beneficial effects of the present invention are:
[0026] The semi-dry viscoelastic sealant provided by the present invention uses polyisobutylene and polyisobutylene amine as main resins, and is added with microcapsules embedded with polyisocyanate. The sealant is a liquid with good thixotropy before use, which is convenient for coating the thread surface and installing the threaded parts. During the thread installation process, the sealant is squeezed by the thread, the microcapsules are broken, and the polyisocyanate core material embedded therein flows out, which can be extended with the polyisobutylene amine and other resins in the sealant to form a high molecular weight compound, so that the liquid sealant is converted into a semi-dry viscoelastic sealant. In this way, the problem of thread jamming and affecting installation when the semi-dry viscoelastic sealant is directly used is completely avoided.
[0027] The present invention uses polyisobutylene resin as the main material, and has excellent dielectric sealing, electrical insulation, lubrication, acid and alkali resistance, corrosion resistance and the like. Self-lubricating fillers are added to the system to facilitate the installation of threads. The use of thickeners can make the sealant have good anti-sagging performance, so that it can effectively fill the thread gaps and is not easy to flow out during use, thereby ensuring the reliability of the seal. The corrosion inhibitor improves the corrosion resistance of the threads.
[0028] The sealant provided by the present invention is a single-component liquid, and no curing agent needs to be added. When used, it is directly coated on the thread surface and then installed, and the use process is simple. After the thread is installed, the liquid sealant can be transformed into a semi-dry viscoelastic state inside the threaded connector, and has good viscoelasticity, self-adhesiveness and self-repairing properties. When used for threaded connectors subjected to large alternating loads in seawater environments, it has high reliability and will not cause sealing failure due to alternating loads and deformation, and seawater medium infiltration will not cause thread corrosion. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A semi-dry viscoelastic sealant, the preparation method is as follows:
[0032] S1. Preparation of polyisocyanate microcapsules:
[0033] S1.1: 5 parts of urea and 18 parts of formaldehyde were mixed and dissolved by weight, and the pH value of the system was adjusted to 8-9 with a 10% sodium carbonate aqueous solution, and the mixture was reacted at 60°C for 60 minutes to obtain a water-soluble urea-formaldehyde resin prepolymer;
[0034] S1.2 0.18 parts of emulsifier Tween-80 was dissolved in 48 parts of water to obtain a continuous phase solution, and then 6 parts of hexamethylene diisocyanate (HDI trimer) were added to the continuous phase solution, and dispersed for 15 minutes using a high-speed shear emulsifier to obtain a stable polyisocyanate emulsion;
[0035] S1.3 adding the water-soluble urea-formaldehyde resin prepolymer obtained in step S1.1 to the polyisocyanate emulsion obtained in step S1.2, adjusting the pH value to 2-3 with glacial acetic acid, and reacting at 60° C. for 2 h to obtain a polyisocyanate microcapsule suspension;
[0036] S1.4 The polyisocyanate microcapsule suspension obtained in step S1.3 is centrifuged to obtain a microcapsule precipitate. The obtained microcapsule precipitate is washed with water and ethanol, and then dried at room temperature to obtain polyisocyanate microcapsules.
[0037] S2. Preparation of semi-dry viscoelastic sealant:
[0038] Calculated by mass, 45 parts of polyisobutylene resin (molecular weight 2000), 25 parts of low molecular weight polyisobutylene amine (molecular weight 1000), 10 parts of lubricating filler (polytetrafluoroethylene), 5 parts of reinforcing filler (nanosilica), 20 parts of pigment filler (titanium dioxide), 4 parts of rust-proof filler (aluminum tripolyphosphate), 1 part of thickener (organic clay), 0.3 parts of wetting and dispersing agent (Haimingsteqian 904S) and 2 parts of corrosion inhibitor (polycarboxylate) are uniformly dispersed by high-speed stirring, ground to a fineness of 30 μm, and then 15 parts of polyisocyanate microcapsules are added and stirred slowly to obtain a semi-dry viscoelastic sealant.
[0039] The semi-dry viscoelastic sealant prepared in this embodiment is coated on the thread surface. The coating amount of the sealant is greater than the actual filling amount of the thread. After the thread is installed, excess sealant is squeezed out. The squeezed sealant is wiped clean with cotton cloth. After the thread is installed, it is left to stand for 2 hours, and the sealant on the inner wall can be converted into a semi-dry viscoelastic state. According to the test conditions of a thread diameter of 50mm and a stress of 60KN, the threaded connector using the semi-dry viscoelastic sealant is subjected to an alternating stress test of 2Hz for 8000 times, and then a 2000h artificial seawater immersion test is carried out. After the test, the thread is disassembled and the thread surface is checked for obvious corrosion.
[0040] Example 2
[0041] A semi-dry viscoelastic sealant, the preparation method is as follows:
[0042] S1. Preparation of polyisocyanate microcapsules:
[0043] S1.1 Take 5 parts of urea and 10 parts of formaldehyde by mass, mix and dissolve them, use 10% sodium carbonate aqueous solution to adjust the pH value of the system to 8-9, react at 60°C for 60 minutes, and obtain a water-soluble urea-formaldehyde resin prepolymer;
[0044] S1.2 0.54 parts of emulsifier gum arabic was dissolved in 108 parts of water to obtain a continuous phase solution, and then 10.8 parts of hexamethylene diisocyanate (HDI trimer) was added to the continuous phase solution, and dispersed for 15 minutes using a high-speed shear emulsifier to obtain a stable polyisocyanate emulsion;
[0045] S1.3 adding the water-soluble urea-formaldehyde resin prepolymer obtained in step S1.1 to the polyisocyanate emulsion obtained in step S1.2, adjusting the pH value to 2-3 with glacial acetic acid, and reacting at 60° C. for 2 h to obtain a polyisocyanate microcapsule suspension;
[0046] S1.4 The polyisocyanate microcapsule suspension obtained in step S1.3 is centrifuged to obtain a microcapsule precipitate. The obtained microcapsule precipitate is washed with water and ethanol, and then dried at room temperature to obtain polyisocyanate microcapsules.
[0047] S2. Preparation of semi-dry viscoelastic sealant:
[0048] Calculated by mass, 60 parts of polyisobutylene resin (molecular weight 2000), 40 parts of low molecular weight polyisobutylene amine (molecular weight 1000), 20 parts of lubricating filler (molybdenum disulfide), 10 parts of reinforcing filler (nanosilica), 30 parts of pigment filler (titanium dioxide), 8 parts of rust-proof filler (aluminum tripolyphosphate), 2 parts of thickener (organic clay), 0.6 parts of wetting and dispersing agent (Haimingsteqian 904S) and 4 parts of corrosion inhibitor (polycarboxylate) are uniformly dispersed by high-speed stirring, ground to a fineness of 30 μm, and then 25 parts of polyisocyanate microcapsules are added and stirred slowly to obtain a semi-dry viscoelastic sealant.
[0049] The semi-dry viscoelastic sealant prepared in this embodiment is applied to the thread surface. The amount of sealant applied is greater than the actual amount of thread filling. After the thread is installed, excess sealant is squeezed out. The squeezed sealant is wiped clean with cotton cloth. After the thread is installed, it is left to stand for 2 hours. The sealant on the inner wall can be converted into a semi-dry viscoelastic state. According to the test conditions of a thread diameter of 50mm and a stress of 60KN, the threaded connector using the semi-dry viscoelastic sealant is subjected to an alternating stress test of 2Hz for 8000 times, and then a 2000h artificial seawater immersion test is carried out. After the test, the thread is disassembled and the thread surface is checked for obvious corrosion.
[0050] Example 3
[0051] A semi-dry viscoelastic sealant, the preparation method is as follows:
[0052] S1. Preparation of polyisocyanate microcapsules:
[0053] S1.1 Take 5 parts of urea and 15 parts of formaldehyde by mass, mix and dissolve them, use 10% sodium carbonate aqueous solution to adjust the pH value of the system to 8-9, react at 60°C for 60 minutes, and obtain a water-soluble urea-formaldehyde resin prepolymer;
[0054] S1.2 Dissolve 0.2 parts of a mixed emulsifier of alkylphenol polyoxyethylene ether (OP-10) and 0.2 parts of sodium dodecylbenzene sulfonate in 90 parts of water to obtain a continuous phase solution, and add 10 parts of HDI trimer to the continuous phase solution, and disperse it for 15 minutes using a high-speed shear emulsifier to obtain a stable polyisocyanate emulsion;
[0055] S1.3 adding the water-soluble urea-formaldehyde resin prepolymer obtained in step S1.1 to the polyisocyanate emulsion obtained in step S1.2, adjusting the pH value to 2-3 with glacial acetic acid, and reacting at 60° C. for 2 h to obtain a polyisocyanate microcapsule suspension;
[0056] S1.4 The polyisocyanate microcapsule suspension obtained in step S1.3 is centrifuged to obtain a microcapsule precipitate. The obtained microcapsule precipitate is washed with water and ethanol, and then dried at room temperature to obtain polyisocyanate microcapsules.
[0057] S2. Preparation of semi-dry viscoelastic sealant:
[0058] Calculated by mass, 55 parts of polyisobutylene resin (molecular weight 2000), 30 parts of low molecular weight polyisobutylene amine (molecular weight 1000), 15 parts of lubricating filler (polytetrafluoroethylene), 8 parts of reinforcing filler (nanosilica), 25 parts of pigment filler (titanium dioxide), 6 parts of rust-proof filler (aluminum tripolyphosphate), 1.5 parts of thickener (organic clay), 0.5 parts of wetting and dispersing agent (Haimingsteqian 904S) and 3 parts of corrosion inhibitor (polycarboxylate) are uniformly dispersed by high-speed stirring, ground to a fineness of 30μm, and then 20 parts of polyisocyanate microcapsules are added and stirred slowly to obtain a semi-dry viscoelastic sealant.
[0059] The semi-dry viscoelastic sealant prepared in this embodiment is applied to the thread surface. The amount of sealant applied is greater than the actual amount of thread filling. After the thread is installed, excess sealant is squeezed out. The squeezed sealant is wiped clean with cotton cloth. After the thread is installed, it is left to stand for 2 hours. The sealant on the inner wall can be converted into a semi-dry viscoelastic state. According to the test conditions of a thread diameter of 50mm and a stress of 60KN, the threaded connector using the semi-dry viscoelastic sealant is subjected to an alternating stress test of 2Hz for 8000 times, and then a 2000h artificial seawater immersion test is carried out. After the test, the thread is disassembled and the thread surface is checked for obvious corrosion.
[0060] Comparative Example 1
[0061] Calculated by mass, 45 parts of polyisobutylene resin (molecular weight 2000), 25 parts of low molecular weight polyisobutylene amine (molecular weight 1000), 10 parts of lubricating filler (polytetrafluoroethylene), 5 parts of reinforcing filler (nanosilica), 20 parts of color filler (titanium dioxide), 4 parts of rust-proof filler (aluminum tripolyphosphate), 1 part of thickener (organic clay), 0.3 parts of wetting and dispersing agent (Haimingsteqian 904S) and 2 parts of corrosion inhibitor (polycarboxylate) are uniformly dispersed under high-speed stirring and ground to a fineness of 30 μm to obtain a liquid sealant.
[0062] When in use, apply liquid sealant on the thread surface. The amount of sealant applied is greater than the actual thread filling amount. After the thread is installed, excess sealant is squeezed out. Use cotton cloth to wipe the squeezed sealant clean. After the thread is installed, let it stand for 2 hours. According to the test conditions of 50mm thread diameter and 60KN stress, the threaded connector using liquid sealant is subjected to 8000 times of alternating stress test at a frequency of 2Hz, and then 2000h artificial seawater immersion test. After the test, the thread is disassembled and the thread surface is checked for obvious corrosion.
[0063] Comparative Example 2
[0064] The commercially available sealant Loctite 243 thread glue was applied to the thread surface, and the amount of application was greater than the actual thread filling amount. After the thread was installed, excess sealant was squeezed out. The squeezed sealant was wiped clean with cotton cloth and the thread was left to stand for 2 hours after installation. According to the test conditions of 50mm thread diameter and 60KN stress, the threaded connector using commercial sealant was subjected to 8000 alternating stress tests at a frequency of 2Hz, and then a 2000h artificial seawater immersion test. After the test, the thread was disassembled and the sealant was destroyed. The thread surface was checked for severe corrosion.
[0065] In summary, the present invention uses polyisobutylene and polyisobutylene amine as the main resin, adds microcapsules embedded with polyisocyanate, and obtains a semi-dry viscoelastic sealant with good viscoelasticity, self-adhesiveness and self-repairing properties, which can be used for the sealing and corrosion protection needs of threaded connectors that withstand large alternating loads in seawater environments. In addition, the present invention adds polyisocyanate in the form of microcapsules, which completely makes up for the problem of directly adding polyisocyanate to prepare a semi-dry viscoelastic sealant, and then using it directly to cause the threads to get stuck, affecting the installation.
[0066] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0067] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A semi-dry viscoelastic sealant, characterized in that: In parts by mass, it includes: 45-60 parts of polyisobutylene resin, 25-40 parts of polyisobutylene amine, 15-25 parts of polyisocyanate microcapsules, 10-20 parts of lubricating fillers, 5-10 parts of reinforcing fillers, 20-30 parts of pigment fillers, 4-8 parts of rust-proof fillers, 1-2 parts of thickeners, 0.3-0.6 parts of wetting and dispersing agents, and 2-4 parts of corrosion inhibitors; The polyisocyanate microcapsules are microcapsules of polyisocyanate encapsulated by urea-formaldehyde resin; the molecular weight of the polyisobutylene resin is 2000-2800, and the molecular weight of the polyisobutylene amine is 800-1000.
2. A semi-dry viscoelastic sealant according to claim 1, characterized in that: The polyisocyanate is hexamethylene diisocyanate.
3. A semi-dry viscoelastic sealant according to claim 1, characterized in that: The preparation method of the polyisocyanate microcapsules comprises the following steps: The urea, formaldehyde and alkaline pH regulator are mixed and subjected to condensation reaction to obtain a urea-formaldehyde resin prepolymer; The emulsifier is dissolved in water to obtain a continuous phase solution, and then the polyisocyanate is added to the continuous phase solution and dispersed at high speed to obtain a polyisocyanate emulsion; The urea-formaldehyde resin prepolymer, polyisocyanate emulsion and acidic pH regulator are mixed and then subjected to curing reaction to obtain urea-formaldehyde resin-wrapped isocyanate microcapsules.
4. A semi-dry viscoelastic sealant according to claim 3, characterized in that: In the preparation of the urea-formaldehyde resin prepolymer, the mass ratio of urea to formaldehyde is 5:(10-18), and the alkaline pH regulator is a 10% sodium carbonate aqueous solution.
5. The semi-dry viscoelastic sealant according to claim 3, characterized in that: In the preparation of the polyisocyanate emulsion, the emulsifier is at least one of Tween-80, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, gum arabic, and alkylphenol polyoxyethylene ether, and the added amount thereof is 3% to 5% of the mass of the polyisocyanate. The mass ratio of polyisocyanate to water in the polyisocyanate emulsion is 1: (8 to 10).
6. A semi-dry viscoelastic sealant according to claim 3, characterized in that: In the preparation of the urea-formaldehyde resin-wrapped isocyanate microcapsules, the acidic pH regulator is glacial acetic acid; the pH value of the curing reaction is 2-3, the reaction temperature is 50-70° C., and the reaction time is 2-3 hours.
7. The method for preparing a semi-dry viscoelastic sealant according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyisobutylene resin, polyisobutylene amine, lubricating filler, reinforcing filler, pigment filler, rust-proof filler, thickener, wetting dispersant and corrosion inhibitor are mixed, dispersed evenly, and ground to a fineness of less than 30 μm to obtain component A; Polyisocyanate microcapsules are added to the A component and mixed evenly to obtain the semi-dry viscoelastic sealant.
8. Use of the semi-dry viscoelastic sealant according to any one of claims 1 to 6 in threaded connectors.
Citation Information
Patent Citations
Anticorrosive thread compound composition and preparation method thereof
CN105018207A
Self-repairing insulating material for electrical equipment and preparation method of self-repairing insulating material
CN116574437A